Habit royal et espaces d’intimité à la cour de Charles II - Sandra Martinez (E-Spania)
At the palace, privacy and private spaces are numerous and their power is as strong as the politic meaning given to them. On the one hand, the most private, the most hidden, the most secret, is the most political, charged with kingdom-wide social and financial issues; on the other hand, the intimate sphere of the monarch is shown, staged and organized in space. The king's private person is invented, like his public person. The king's habit seems to impose a border of interiority, both physical and symbolic, while being the instrument for the creation of a public image. That is what makes all the singularity of this powerful and eloquent visual object. Gateway to the daily life of the sovereign, at the crossroads of several trades of craftsmen, merchants and employees of the king's houses, the habit creates unique links. Some palace employees, through the royal garment service, can gain privileged proximity to the king's body and develop a relationship of contact and trust. The object of the article is to measure the meaning that royal adornment gives to the intimacy, real or invented, of the sovereign at the Madrid court of the end of the 17th Century.